The Description of Social Functioning in Working Students - Hanastasya Stephanie Lucky; Ira Darmawanti (Character Jurnal Penelitian Psikologi, 2023)
The purpose of this study is to describe the social functioning of working students. The approach used in this study uses a qualitative approach with the case study method. Data collection was carried out using semi-structured interviews to dig deeper data about the participants. The participants used were 2 students who met the criteria, namely having full-time work experience in the first semester of college. In this study using thematic analysis as a data analysis technique in it. Test the validity of the data used is member checking. The results obtained in this study indicate that there is a role played by both students and workers resulting in these working students experiencing several impacts such as fatigue, procastination, and negligence in doing household chores. These three things interfere with social functioning because they harm themselves and others. The involvement of family, peer, and social media care influences individuals in carrying out their social functioning so that this becomes an important factor for the social functioning of working students Key word : social function, load, student work